ANALISIS KUALITAS FAKTA DAN KUALITAS PERSEPSI GURU DALAM MENINGKATKAN MUTU PENDIDIKAN BERBASIS SIM DI SDN 067240 TEMBUNG TP 2020/2021 - Syafaruddin Syafaruddin; Makmur Syukri; Ahmad Risqi (Universitas Indraprasta PGRI, 2022)
In actual quality, manufacturers show that quality has a system, which can be called a quality assurance system, that allows the production wheel to consistently produce products according to certain standards or specifications. Thus a product is said to be of high quality as long as the product is consistent with the demands of the maker. Meanwhile, in terms of perceived quality, quality is defined as something that satisfies or exceeds customer desires. In this case, it is the customer who determines or evaluates a quality product or service. This study aims to obtain information about Teacher's Perception of Academic Quality Improvement Based on Management Information Systems at SD Negeri 067240 Tembung in terms of aspects: quality and management information systems. This type of research is descriptive research. The population of this study were all 11 teachers at SD Negeri 067240 Tembung. The research method is descriptive qualitative. Data was collected by observation and interviews with teachers and staff at the school. The results showed that: 1. Teachers' perceptions of improving the quality of education at SD Negeri 067240 Tembung were considered weak. The number of those who complain that they are not capable and lack of expertise makes the quality of education in these schools decline. 2. Teachers' perceptions of using Management Information Systems in schools are also considered weak. Some senior teachers who only rely on school operators make the information system not run as smoothly as it should